Testosterone level and histological features of tualang honey and nicotine treated male rats. - Noorhafiza, R.; Majid, A.M.; Hashida, N.H. (2013)
Forty-four Sprague-Dawley rats were divided into honey (1.0ml/100g honey), honey control (1.0ml/100g 0.9% NaCl), nicotine (0.5mg/100g nicotine), nicotine control (0.1ml/100g 0.9% NaCl) and nicotine-honey (0.5mg/100g nicotine and 1.0ml/100g honey) groups and treated for 60 days. On day 61, the rats were sacrificed and blood was drawn for blood hormone analysis. The testes were fixed in Bouin’s solution followed by Hematoxylin and Eosin (H&E) staining technique. This treatment did not significantly affect the testosterone level for all five groups (p≥0.05). The N (263.79±2.17μm) group showed significantly lower diameter of seminiferous tubules compared to the other four groups. The NH (135.02±1.66μm) and HC (130.61±2.05μm) groups were observed to have significantly higher diameter of lumen. The H (34.96±0.40μm) group showed significantly larger width of spermatocytes compared to the N and NH groups (p<0.05). Densely packed and abundant spermatogenic cells were observed in the H, HC, NC and NH treated rats. Degeneration of spermatogenic cells,lower numbers of Leydig and Sertoli cells were observed in the N group. ThSese findings imply that Tualang honey can significantly improve the spermatogenesis process in rats and suggest its potential healing properties to reduce the effects of nicotine in humans.